Tingkat Pengetahuan dan Perilaku Swamedikasi Batuk Pilek Mahasiswa Farmasi Angkatan 2019 Universitas Sari Mulia dengan Metode TPB - Kurniawati, Darini; Charmelya, Estyvania Nur; Tangkas, Hansel Hens; Panjaitan, Pungky Angeliana Putri (Universitas PGRI Adi Buana, Surabaya, 2022)
AbstractCoughs and colds are a response the body created to get rid of foreign objects, including viruses, dust, mucus, and other small particles that try to contaminate the respiratory tract starting from the throat to the lungs. Cough symptoms can be treated with self-medication, which is a self-medication process carried out by a person starting from the introduction of complaints or symptoms to the selection and use of drugs. There are methods that can beused to treat coughs and colds, namely pharmacological methods (drug therapy) and nonpharmacological methods (non-drug therapy). The theory used can be observed, namely the method of Theory of Planned Behavior or TPB (Theory of Planned Behavior). The purpose of this activity is to increase students' knowledge and skills in dealing with coughs and colds. So that it is expected to provide information and treatment in making efforts to prevent cough and cold symptoms. This type of research is observational research with descriptive research methods. The approach used is cross sectional. The level of knowledge of the 2019 batch of pharmacy students at Sari Mulia University Banjarmasin about self-medication for cough and cold with a good category of 23 respondents, 22 percent, with a sufficient category of 63 respondents (62 percent), and a less category as many as 16 respondents, 16 percent . From these results, it is hoped that the institution will further deepen and evaluate after learning or lecturesin order to maximize the material obtained, it is hoped that students apply and relearn what they have learned so that their knowledge is good, and it is also hoped that future researchers can investigate further about rationality. self-medication actions taken by students.